Formononetin-induced Apoptosis of Human Prostate Cancer Cells Through ERK1/2 Mitogen-activated Protein Kinase Inactivation - Ye, Y.; Hou, R.; Chen, J.; Mo, L.; Zhang, J.; Huang, Y.; Mo, Z. (Hormone and Metabolic Research, 2012)
Formononetin is a main active component of red clover plants (Trifolium pratense L.), and is considered as a phytoestrogen. Our previous studies demonstrated that formononetin caused cell cycle arrest at the G0/G1 phase by inactivating insulin-like growth factor 1(IGF1)/IGF1R-phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway in MCF-7 cells. In the present study, we investigated the molecular mechanisms involved in the effect of formononetin on prostate cancer cells. Our results suggested that higher concentrations of formononetin inhibited the proliferation of prostate cancer cells (LNCaP and PC-3), while the most striking effect was observed in LNCaP cells. We further found that formononetin inactivated extracellular signal-regulated kinase1/2 (ERK1/2) mitogen-activated protein kinase (MAPK) signaling pathway in a dose-dependent manner, which resulted in increased the expression levels of BCL2-associated X (Bax) mRNA and protein, and induced apoptosis in LNCaP cells. Thus, we concluded that the induced apoptosis effect of formononetin on human prostate cancer cells was related to ERK1/2 MAPK-Bax pathway. Considering that red clover plants were widely used clinically, our results provided the foundation for future development of different concentrations formononetin for treatment of prostate cancer.
Keywords: formononetin; phytoestrogen; IGF-1R; prostate cancer; ERK1/2